Feasibility of Single-Staged Bilateral Anterior Scoliosis Correction in Growing Patients. Issue 1 (January 2021) - Baroncini, Alice; Rodriguez, Luis; Verma, Kushagra; Trobisch, Per D.
Study Design: Retrospective analysis. Objectives: The objective of this study was to analyze the feasibility of correcting double-curve scoliosis using dynamic scoliosis correction (DSC, also known as vertebral body tethering), which requires a bilateral anterior approach with deflation of both lungs. Typically, this approach falls under the exclusionary criteria for the eligibility for anterior scoliosis surgery. No data exists on the feasibility of single-staged bilateral DSC. Methods: A retrospective analysis was performed utilizing the data from 25 patients who underwent a bilateral anterior thoracic approach and instrumentation. Thirty-day postoperative complication rates were analyzed. A learning curve subanalysis was also performed to compare the first 12 patients to the remainder of the 13 patients, with a T -test ( P ≤ .05). Results: Of the 25 patients treated, there was 1 intraoperative event: After performing lumbar DSC, the contralateral DSC was abandoned due to unexpected pleural scarring and staged selective thoracic fusion was performed. We observed 4 postoperative complications: 2 patients had recurrent pleural effusions, 1 patient was diagnosed with pneumonia, and 1 patient had a minor pulmonary embolism without cardiopulmonary consequences (after an international 24 hour flight). All patients recovered well. We observed a significant influence of learning curve on surgical time (328 vs 280 min, P = .03) and blood loss (480 vs 197 mL, P = .03). Conclusion: Data suggests that bilateral, single-stage surgery for DSC is feasible albeit with an elevated complication rate that may partially attributable to the learning curve. Future research should focus on the cause of pulmonary complications and include a matched comparative analysis with traditional posterior fusion.